How does alzheimer's disease, atherosclerosis and comorbid alzheimer's disease and atherosclerosis impact neurovascular function?. (20th December 2022) - Eyre, Beth; Shabir, Osman; Lee, Llewelyn; Francis, Sheila; Howarth, Clare; Berwick, Jason
Abstract: Background: The brain is an energy hungry organ, consuming approximately 20% of the body's energy supply (Clark & Sokoloff 1999). Due to its high energy demands the brain has developed a critical mechanism termed neurovascular coupling (NVC). NVC is the relationship between neuronal activity and a subsequent increase in blood flow to the same brain region. This mechanism is suggested to be impaired in many disorders, including Alzheimer's disease (AD) (Kisler et al., 2017). Additionally, approximately 90% of individuals living with dementia have a comorbidity (Browne et al., 2017), with some of the most common comorbidities being cardiovascular disease (Tini et al., 2020) and type 2 diabetes (Santiago et al., 2021). Therefore, we wanted to investigate neurovascular function in AD and comorbid mixed models of AD and atherosclerosis. Method: Four separate groups of mice were used, aged 9‐12 months: AD (APP/PS1 (B6;C3 Tg(APPswe, PSEN1dE9)85Dbo/Mmjax)), WT (APP/PS1‐WT littermates), atherosclerosis (WT + rAAV8‐mPCSK9‐D377Y + Western Diet) and Mixed AD and atherosclerosis (APP/PS1 + rAAV8‐mPCSK9‐D377Y + Western Diet). At 9m mice completed the novel object recognition test (NOR) to assess cognition. Following this, a thinned window surgery was completed. One‐week post‐surgery 2‐dimensional optical imaging spectroscopy (2D‐OIS) was utilised to investigate changes in cerebral haemodynamics, in response to a whisker stimulation in awake mice. A separate imaging session in anaesthetised mice was also completed, using 2D‐OIS concurrent with electrophysiology to assess neurovascular coupling. Immunohistochemistry was performed to assess amyloid plaque load within the brain. Result: In the awake imaging session we found that neurovascular function was preserved in the AD group. However, mice in the atherosclerosis group showed a reduction in blood volume in response to a 2s‐whisker stimulation, compared to the WT group. We hypothesised that the mixed model would have the greatest impairment in the neurovascular response, however this was not observed and this group showed an evoked‐blood volume change in between levels of AD and atherosclerosis only groups. Conclusion: Preliminary results suggest that neurovascular function is impaired in mouse models of atherosclerosis but not in the AD or mixed models. Analysis is ongoing to determine how neural activity and AD pathology are impacted by comorbidity.